THERMAL MANAGEMENT OF THE HYBRID MEMORY CUBE - Khurshid, Mushfique (My University, 2013)
Main memory performance is becoming an increasingly important factor contributing to overall system performance, especially due to the so-called memory wall. The Hybrid Memory Cube (HMC) is a novel 3D heterogenous architecture of DRAM, designed to improve DRAM performance, consisting of DRAM dies stacked on top of each other, with a logic die at the bottom - all interconnected with highly dense through silicon vias (TSVs). This logic die communicates with an on chip memory controller for receiving/sending requests using high speed links. Modelling the Hybrid Memory Cube in HotSpot has indicated that this cube has a natural temperature variation, with the hottest layers at the bottom and the cooler layers at the top. High temperatures and variations within a DRAM can result in reduced performance and efficiency, especially when dynamic thermal management (DTM) schemes are used to throttle DRAM bandwidth whenever temperature gets too high. Hence this dissertation attempts to reduce the maximum temperature and also this variation, by using data compression - where the compression is performed on the on chip memory controller, and the compressed blocks are read/written using fewer bursts in the Hybrid Memory Cube, hence reducing power dissipation. Compressed blocks are stored only in the hotter banks of the cube to mitigate the thermal gradient in the cube. Maximum temperature was reduced by as much as 6 C, and since the HMC spent lesser time throttling when DTM schemes were used, a maximum of 12.5% reduction in execution time was observed, at an average reduction of 2.6%.